Some Important Insect Pests of Poplars in the Western Himalayas and their Management - Sharma, Ajay; Verma, T. D.; Sood, Anil (Indian Forester, 2005)
Poplars hold an important place in the agroforestry systems because of their multiple use, fast growing nature and short rotation. Tbey are being grown on large scale in the plains of nortbern India, valley area of Himachal Pradesh and Jammu & Kashmir. Different Poplar clones being grown on these areas are invariably attacked by a number of insect pests. Various insect species invade Poplar plant parts right from the nursery stage to the maturity of the crop. Some of the important inseet pests infesting these trees include Apriona cinerea, Eucosma glaciuta, Plagiodera versicolora etc. They not only affect the growth and render them unfit for proper utilization but also sometimes threat their survival. An account of insect pests associated with Poplars in western Himalayan region in respect of their incidence, nature and extent of damage and management strategies have been discussed in the text.